2022
DOI: 10.14778/3551793.3551831
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm and system co-design for efficient subgraph-based graph representation learning

Abstract: Subgraph-based graph representation learning (SGRL) has been recently proposed to deal with some fundamental challenges encountered by canonical graph neural networks (GNNs), and has demonstrated advantages in many important data science applications such as link, relation and motif prediction. However, current SGRL approaches suffer from scalability issues since they require extracting subgraphs for each training or test query. Recent solutions that scale up canonical GNNs may not apply to SGRL. Here, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…r f 6 8 j p p X 1 W 9 6 2 q t W a v U S R 5 H E c 7 g H C 7 B g x u o w z 0 0 o A U M E J 7 h F d 6 c R + f F e X c + l q 0 F J 5 8 5 h T 9 w P n 8 A 2 m G M 4 A = = < / l a t e x i t > u < l a t e x i t s h a 1 _ b a s e 6 4 = " 9 / b v X 4 5 X T 9 a Z V + w 8 r s Y i k q J X / L s = " > A A A B 6 H i c b V B N S 8 N A E J 3 U r 1 q / q h 6 9 L B b B U 0 l E 1 G P B i 8 c W 7 A e 0 o W y 2 k 3 b t Z h N 2 N 4 U S + g u 8 e F D E q z / J m / / G b Z u D t j 4 Y e L w 3 w 8 y 8 ple for Link Prediction. SUREL+ samples node sets while SEAL [54,57] extracts the whole subgraph for each query and SUREL [51] samples walks. To serve node set-based representations, SUREL+ designs a new algorithm with dedicated system support.…”
Section: Modular Designmentioning
confidence: 99%
See 2 more Smart Citations
“…r f 6 8 j p p X 1 W 9 6 2 q t W a v U S R 5 H E c 7 g H C 7 B g x u o w z 0 0 o A U M E J 7 h F d 6 c R + f F e X c + l q 0 F J 5 8 5 h T 9 w P n 8 A 2 m G M 4 A = = < / l a t e x i t > u < l a t e x i t s h a 1 _ b a s e 6 4 = " 9 / b v X 4 5 X T 9 a Z V + w 8 r s Y i k q J X / L s = " > A A A B 6 H i c b V B N S 8 N A E J 3 U r 1 q / q h 6 9 L B b B U 0 l E 1 G P B i 8 c W 7 A e 0 o W y 2 k 3 b t Z h N 2 N 4 U S + g u 8 e F D E q z / J m / / G b Z u D t j 4 Y e L w 3 w 8 y 8 ple for Link Prediction. SUREL+ samples node sets while SEAL [54,57] extracts the whole subgraph for each query and SUREL [51] samples walks. To serve node set-based representations, SUREL+ designs a new algorithm with dedicated system support.…”
Section: Modular Designmentioning
confidence: 99%
“…Given a set of nodes of interest, namely a queried node-set, SGRL models such as SEAL [54,57], GraIL [41], and SubGNN [1] first extract a subgraph around the queried node-set (termed query-induced subgraph), and then encode the extracted subgraph for prediction. Extensive works have shown that SGRL models are more robust [52] and more expressive [5,12]; while canonical graph neural networks (GNNs) including GCN [23] and GraphSAGE [14] generally fail to make accurate predictions, due to their limited expressive power [9,13,57], incapability of capturing intra-node distance information [28,39], and improper entanglement between receptive field size and model depth [18,51,52]. An example in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve SubGNN by distinguishing nodes inside and outside the subgraph, GNN with LAbeling trickS for Subgraph (GLASS) [37] utilizes an expressive and scalable labeling trick to enhance GNNs for subgraph representation learning. Most recently, to address the scalability issue in the subgraph representation learning problem via GNNs, SUREL [38] reduces the redundancy of subgraph extraction and supports parallel processing by decoupling the graph structure into sets of walks and reusing the walks to form subgraphs.…”
Section: Static Network Representation Learningmentioning
confidence: 99%
“…To improve SubGNN by distinguishing nodes inside and outside the subgraph, GLASS [50], GNN with LAbeling trickS for Subgraph, utilizes an expressive and scalable labelling trick to enhance GNNs for subgraph representation learning. Very recently, to address the scalability issue in the subgraph representation learning problem via GNNs, SUREL [51] reduces the redundancy of subgraph extraction and supports parallel processing by decoupling the graph structure into sets of walks and reusing the walks to form subgraphs.…”
Section: Subgraph Representation Learningmentioning
confidence: 99%